New reference values for the 6-minute walk distance in a European population across the full adult age range - De Soomer, Kevin; Geubels, Kaat; Mendoza, Hilbert; Wener, Reinier; Lapperre, Thérèse; Oostveen, Ellie (Respiratory medicine, 2025)
The 6-min walk test (6MWT) is widely used to evaluate functional exercise capacity in individuals of all ages. However, there are currently no widely accepted reference values for the 6-min walk distance (6MWD) in White populations across the full adult age range, as most existing predictions are derived from selected age groups. This study aimed to develop 6MWD reference equations for European populations covering the entire adult lifespan. Healthy adults, equally distributed for sex and age, performed a single 6MWT according to current guidelines. The effects of sex, age, height, weight and BMI on the 6MWD were analysed. The 6MWT was performed in 212 subjects (51 % females, age: 18–87 yrs). Males walked a greater distance than females with a mean ± SD 6MWD of 697 ± 83 m and 629 ± 72 m, respectively (p < 0.001). In both sexes, the 6MWD was not affected by age below 50 years whereas it declined progressively beyond this age. Height and BMI linearly correlated with the 6MWD in males and females (both p < 0.001) while weight was only related to the 6MWD in males (p = 0.02). A reference equation was developed using stepwise multiple regression, with sex, age, age2, height and weight as significant predictors of the 6MWD (R2 = 0.548). In the present study, we observed a non-linear ageing effect on the 6MWD throughout adulthood. The developed reference equation accounts for this effect and should be considered in settings where a single 6MWT is performed in European adults of all ages. •New 6MWD reference values developed for Europeans across the full adult age spectrum.•A reference equation is proposed for the interpretation of one-time 6MWT assessments.•6MWD decline with age mainly occurs after middle age, not in a linear pattern.